Work-related biomechanical exposure and job strain in midlife separately and jointly predict disability after 28 years: a Finnish longitudinal study - KC Prakash; Subas Neupane; Päivi Leino-Arjas; Mikaela B von Bonsdorff; Taina Rantanen; Monika E von Bonsdorff; Jorma Seitsamo; Juhani Ilmarinen; Clas-Håkan Nygård (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: We investigated whether the extent of biomechanical exposures and job strain in midlife separately and jointly predict disability in old age. METHODS: Participants of the Finnish Longitudinal Study on Aging Municipal Employees (FLAME) in 1981 (aged 44-58 years) responded to disability questionnaires in 2009 (1850 women and 1082 men). Difficulties in performing five activities of daily living (ADL) and seven instrumental ADL (IADL) were used to assess severity of disability (score range: 0-12, 0=no disability). Information on biomechanical exposures and job strain was collected by questionnaire at baseline. Adjusted prevalence proportion ratios (PR) and 95% confidence intervals (95% CI) were modelled using mixed negative binomial regression with robust variance. The joint effect of two exposures was quantified using the concept of relative excessive risk due to interaction (RERI). RESULTS: The overall prevalence of disability (score: 1-12) was 46.7% (women: 41%; men: 57%). Compared to low-level exposures in an adjusted model, the PR of high baseline biomechanical exposures for each one unit increase in the disability score was 1.31 (95% CI 1.10-1.55) and PR of high job strain was 1.71 (95% CI 1.26-2.32). Associations were rather similar in gender-stratified analyses. Furthermore, the joint effect (high strain/high biomechanical) was multiplicative (women: PR 1.32, 95% CI 1.21-1.45; men: PR 1.27, 95% CI 1.13-1.44), but no additive effect was observed when fully adjusted. CONCLUSION: High biomechanical exposure and job strain in midlife were strongly associated with the severity of disability in later life. The workplace could serve as arena for preventive interventions regarding disability in old age.